Spring Viremia of Carp - Barbara D. Petty; Ruth Francis-Floyd; Roy P. E. Yanong (EDIS)
Spring viremia of carp is a viral disease that can cause significant mortality in several carp species including the common carp. It was reported in koi and feral carp in the United States for the first time in 2002. Diagnosis in farm raised fish in the U.S. may result in quarantine of the infected fish and depopulation. This revised 5-page fact sheet is intended to inform veterinarians, biologists, culturists, and hobbyists about Spring viremia of carp. Written by Barbara D. Petty, Ruth Francis-Floyd, and Roy P.E. Yanong, and published by the UF Department of Fisheries and Aquatic Sciences, August 2012.